Discovery of sustainable drugs for Alzheimer's disease: cardanol-derived cholinesterase inhibitors with antioxidant and anti-amyloid properties. Issue 7 (5th May 2021) - de Andrade Ramos, Giselle; Souza de Oliveira, Andressa; Bartolini, Manuela; Naldi, Marina; Liparulo, Irene; Bergamini, Christian; Uliassi, Elisa; Wu, Ling; Fraser, Paul E.; Abreu, Monica; Kiametis, Alessandra Sofia; Gargano, Ricardo; et al.
Abstract : A series of cardanol derivatives has been developed from an inexpensive food waste material ( i.e., cashew nut shell liquid, CNSL) to generate cholinesterase inhibitors with concomitant anti-amyloid and anti-oxidative activities and no cytotoxicity. Abstract : As part of our efforts to develop sustainable drugs for Alzheimer's disease (AD), we have been focusing on the inexpensive and largely available cashew nut shell liquid (CNSL) as a starting material for the identification of new acetylcholinesterase (AChE) inhibitors. Herein, we decided to investigate whether cardanol, a phenolic CNSL component, could serve as a scaffold for improved compounds with concomitant anti-amyloid and antioxidant activities. Ten new derivatives, carrying the intact phenolic function and an aminomethyl functionality, were synthesized and first tested for their inhibitory potencies towards AChE and butyrylcholinesterase (BChE). 5 and 11 were found to inhibit human BChE at a single-digit micromolar concentration. Transmission electron microscopy revealed the potential of five derivatives to modulate Aβ aggregation, including 5 and 11 . In HORAC assays, 5 and 11 performed similarly to standard antioxidant ferulic acid as hydroxyl scavenging agents. Furthermore, in in vitro studies in neuronal cell cultures, 5 and 11 were found to effectively inhibit reactive oxygen species production at a 10 μM concentration. They also showed a favorable initial ADME/Tox profile. Overall, these results suggest that CNSL is a promising raw material for the development of potential disease-modifying treatments for AD.